E-business solutions and OSS for the SMEs - Z. Havlíček; E. Šilerová; Č. Halbich (Agricultural Economics (AGRICECON), 2008)
www technologies are developing very fast. The new technologies make possible the easier creation of the web applications, which support business activities. Small and medium size enterprises, which serve as the driving force for innovations and thus for economic development, can utilize these technologies for the creation of relatively inexpensive applications, which can be tailor-made for the given enterprise by using the open source software (OSS). This contribution presents several practical examples of how to create - update - the web site of an enterprise and how to supplement it with an e-shop option. Examples from the area of flower selling have been selected.